1 GHz Low-Noise Hybrid Preamplifier for Optical Detection. (1980) - Monti, O.; Scavennec, A.; le Men, P.
Abstract : A 1 GHz low- noise preamplifier, especially designed for photodetection purposes is described. The amplifier noise which sets a limit to the sensitivity of the photodiode-preamplifier combination is minimized using a hybrid technology which allows very low values of the parasitics. Results on a complete photodiode-equalized preamplifier are given.